2013
DOI: 10.4314/bajopas.v5i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Naphthalene Acetic Acid (NAA) on in vitro rooting of regenerated microshoots of groundnut (<i>Arachis hypogaea</i> L.)

Abstract: Successful utilization of tissue culture for the improvement and conservation of groundnut will be made possible only with an efficient shoot proliferation, formation of well-developed root system in microshoots, successful acclimatization and final establishment in field. A regeneration protocol ensuring a high frequency rooting of microshoots derived from embryonic axes of four groundnut genotypes was achieved using naphthalene acetic acid (NAA). Microshoots of 3cm length were subcultured on Murashige and Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The observed differences among the genotypes could be due to genotypic influence, as tissue culture response in groundnut is strongly influenced by the plant genotype [22,23]. Genotypic influence has also been reported in cryopreserved embryonic axes of maize [24]. There was a significant interaction between the genotypes and time of desiccation for moisture content of cryopreserved embryonic axes of groundnut.…”
Section: Resultsmentioning
confidence: 84%
“…The observed differences among the genotypes could be due to genotypic influence, as tissue culture response in groundnut is strongly influenced by the plant genotype [22,23]. Genotypic influence has also been reported in cryopreserved embryonic axes of maize [24]. There was a significant interaction between the genotypes and time of desiccation for moisture content of cryopreserved embryonic axes of groundnut.…”
Section: Resultsmentioning
confidence: 84%
“…It is shown that the regeneration protocol improved by this experiment is more proper for commercial use than established report (Singh et al, 2009) because of minimum use of hormone concentration. An efficient shoot proliferation is made possible with a well-developed rooting system for successful acclimatization and finally it can be established in field (Abdulmalik et al, 2012). Mostly, NAA and IAA were used in different concentrations in full and 1/2 strength of MS basal medium (Fotopoulos and Sotiropoulos, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Abdulmalik et al (2012) on Arachis hypogaea L. reported that rooting was significantly influenced by the presence and concentration of NAA. Microshoots subcultured on medium supplemented with 1 mg l -1 NAA rooted within 2 weeks of subculture, producing the highest number of roots/plantlet and root-induction frequency.…”
Section: Rooting Stagementioning
confidence: 99%